AMMI and SREG analysis for protein content in Vigna unguiculata (L.) Walp - Cardona–Ayala, Carlos (Revista Ciência Agronômica, 2021)
Identifi cation of cowpea genotypes with high protein content for specifi c environments, based on the genotype-environment interaction, has a positive impact in places where access to protein for human consumption is defi cient. The objective of the study was to analyze the protein content of 10 cowpea bean genotypes in fi ve environments in the Caribbean Region of Colombia. The randomized complete block design with four replications at each site was used. The analysis of the genotype-environment interaction (GEI) was performed using the AMMI (additive main effects and multiplicative interaction) and SREG (regression in sites) models, in which the main effects of genotypes (G) + GEI are part of the bilinear term of the model. The AMMI and SREG models and their biplots were useful in the analysis and interpretation of the protein content of cowpea beans from experiments carried out in multiple environments. The AMMI model identifi ed genotypes 1, 4 and 8 as those with the greatest adaptability and stability, and the Montería (MO7B), Mahates (MA7B) and Cereté (CE7B) environments as the most favorable. The SREG model identified a potential mega-environment constituted by the PN7B, MA7B and CE7B environments, in which genotypes 1, 2 and 3 presented greater adaptability and stability, while genotype 8 showed specifi c adaptability in MO7B. In both models, genotypes 6, 7 and 10 showed absence of adaptability and stability in the studied environments.